Algumas aproximações do modelo cognitivo das emoções de Aaron T. Beck com a filosofia, a biologia evolutiva e as neurociências - Lima, Ana Carolina Rimoldi de (2011)
This work consisted of a bibliographic research, that the purpose was elucidate the cognitive model of emotions by Aaron T. Beck, showing relations and parallels between this model to others theoretical approaches of Philosophy and Biology (evolution and cognitive neurosciences) which either are applied to the understanding of the relation between affective and cognitive processes. From the readings of many general texts about emotions and its relations to cognitive processes, was made a selection of philosophical and biological theories that show an interface with the cognitive‟s theory and therapy, of which in Philosophy were considered the approaches of Plato, Aristotle, Descartes and Kant, in Biology, the evolutionary approach of Darwin, few considerations of neo-Darwinists authors and the neuroscientific approaches of Antonio Damasio and Joseph Ledoux. The research method involved, this way, the identification and location of relevant bibliographic material, followed by its collection, through the book reports of each selected theory, and its subsequent explanation. At the end of the explanations of all theories, was made a general discussion of the Beck‟s cognitive model of emotions that is related or have parallels with Philosophy and Biology theories. Was observed that the philosophical approaches considered support the main premise of the cognitive model the cognitive centrality while the evolutionary approaches justify the comprehension of human psychology into fitted and unfitted terms, which is clear in whole Beck‟s cognitive therapeutic. The approaches of the cognitive neurosciences, on the other hand, beyond support some premises, could still provide an empiric substratum (based on the anatomy and the neurochemical operation of the brain) to the main concepts of Beck‟s theory. Concludes, that Beck‟s cognitive model was developed combining his clinical practice results to a consistent theoretical basis, which is related to different concepts of knowledge areas, the current status of his model is a global approach of the human psychology, seeking to understand the pathological and normal psychological processes on a continuum and mutual interaction and, finally, its future development could be related to coming data approaches of neuroscientific researches. It should be noted that this work doesn‟t exhaust the possibilities to comprehend the Beck‟s cognitive model of emotions. Other research, both theoretical and empirical should be undertaken looking the development of cognitive‟s theory and therapy.